Providing A Technical Solution to Improve Nurses' Performance in Drug Delivery : A qualitative study - Fatemeh Kiani; Alireza Shahsavani; Zeinab Barahoui (ACHSM, 2021)
Background and Purpose: Providing services in the nursing profession is very wide. In the field of clinical services, one of the most important is to provide care related to medication, which in fact is one of the ways to assess the quality of nursing care, so this study aims to provide a solution. Technical measures were taken to improve the performance of nurses in the drug delivery process in hospitals affiliated to Zahedan University of Medical Sciences in Iran Materials and Methods: This study was conducted with a qualitative approach and contractual content analysis method in 2017-18. Participants were 16 nurses and a physician working in different wards of the hospital who were included in the study by purposive sampling. The method of data collection was semi-structured interviews. All interviews were conducted and reviewed and analyzed by contractual content analysis. Results: In the present study, "steps to prevent drug error" as the main category and "acting professionally" and "providing technical solutions" as two subcategories were extracted from the data. Conclusion: The results showed that the use of nurses 'experience and knowledge as technical solutions to prevent drug errors can play an important role in improving nurses' performance and increasing patient safety